2022
DOI: 10.1371/journal.pone.0276296
|View full text |Cite
|
Sign up to set email alerts
|

Double functionalized haemocompatible silver nanoparticles control cell inflammatory homeostasis

Abstract: Infection, trauma, and autoimmunity trigger tissue inflammation, often leading to pain and loss of function. Therefore, approaches to control inflammation based on nanotechnology principles are being developed in addition to available methods. The metal-based nanoparticles are particularly attractive due to the ease of synthesis, control over physicochemical properties, and facile surface modification with different types of molecules. Here, we report curcumin conjugated silver (Cur-Ag) nanoparticles synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The findings of the FTIR study have generally recognized the existence of carbonyl groups from the amino acid residues of plants, therefore, indicating the role played by plant proteins and other phytochemicals in the biosynthesis of AgNPs. It is difficult to figure out the role of a specific phytochemical [ 21 ]. Referring to the literature, AgNP preparation from H. thebaica fruit extract gave larger particle sizes reaching 70 nm [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the FTIR study have generally recognized the existence of carbonyl groups from the amino acid residues of plants, therefore, indicating the role played by plant proteins and other phytochemicals in the biosynthesis of AgNPs. It is difficult to figure out the role of a specific phytochemical [ 21 ]. Referring to the literature, AgNP preparation from H. thebaica fruit extract gave larger particle sizes reaching 70 nm [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Helium gas was used as the vehicle for plasma generation. The amount of aqueous reactive species produced in the target solution was measured using the RONS assay kit (OxiSelect™, Cell Biolabs Inc.) following the manufacturer's instructions and previously published literature 17,18 . A 2′, 7′‐dichloro‐dihydro‐fluorescein (DCF) standard curve was used to quantify reactive species production.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the engineered properties like shape, size, surface charge, surface roughness, and surface chemistry of nanomaterials also have significant effects on the immunological responses. Regardless of the core material, the smaller the particle size is, the greater is the material’s capacity to penetrate biological barriers and provoke an inflammatory reaction. , The engineered nanomaterials are reported to carry and locally deliver immunosuppressive agents. In addition to the above beneficial effects, the interaction between nanomaterials and the immune system can be adverse in nature if the nanomaterials are not designed with desired properties.…”
Section: Nanomaterials-mediated Anti-inflammatory Response and Immune...mentioning
confidence: 99%
“…The cytotoxic behavior of nanomaterials mainly depends on their several physicochemical properties including morphology, shape, size, surface chemistry, surface area, composition, and action mechanism. ,,,, Results revealed that exposure of nanomaterials induces ROS generation in a pro-inflammatory state, which further leads to membrane, protein, and lipid damage. Immune system continuous activation causes the development of several allergic and autoimmune diseases.…”
Section: Complications Associated With Nanomaterials-mediated Immune ...mentioning
confidence: 99%